Body language - Ryan, Kathleen O.; Schrank, Louise Welsh; Learning seed (Chicago : Learning Seed, 2008)
Part 1, beyond words will be aguide through the land of wars, invisible bubles, subsconscious gestures, silent language, the rules of eye contact, and invisible grammar. Part 2, reading people will learn about paralanguage, eye behaviour, cultural differences, touch, space and time
part 1. Beyond words.- part 2. Reading people
Title from title screen
With English subtitle
Narration: Anne Gallagher
Keywords: Body language; Nonverbal communication; Communication